Involvement of Intracellular pH in Vascular Insulin Resistance - Ramírez, Marco A.; Beltrán, Ana R.; Araya, Jorge E.; Cornejo, Marcelo; Toledo, Fernando; Fuentes, Gonzalo; Sobrevia, Luis (Current Vascular Pharmacology, 2019)
The maintenance of the pH homeostasis is maintained by several mechanisms including the efflux of protons (H+) via membrane transporters expressed in almost all mammalian cells. Along these membrane transporters the sodium/H+ exchangers (NHEs), mainly NHE isoform 1 (NHE1), plays a key role in this phenomenon. NHE1 is under modulation by several environmental conditions (e.g. hyperglycaemia, protein kinase C activity) as well as hormones, including insulin. NHE1 activation causes intracellular alkalization in human endothelial cells leading to activation of the endothelial Nitric Oxide Synthase (eNOS) to generate NO. Intracellular alkalization is a phenomenon that also results in upregulation of the glucose transporter GLUT4 in cells that are responsive to insulin. A reduction in the removal of the extracellular D-glucose is seen in states of insulin resistance, such as in diabetes mellitus and obesity. Since insulin is a potent activator of eNOS in human endothelium, therefore causing vasodilation, and its vascular effect is reduced in insulin resistance it is likely that a defective signal to activate NHE1 in insulin target cells is expected. This phenomenon results in lower redistribution and activation of GLUT4 leading to reduced uptake of D-glucose and hyperglycaemia. The general concept of a role for NHE1, and perhaps other NHEs isoforms, in insulin resistance in the human vasculature is proposed.
Keywords: endothelium